Topology optimization of cellular materials with periodic microstructure under stress constraints - Coelho, Pedro G. (2019)
This work was partially supported by Fundacao para a Ciencia e a Tecnologia (Portugal) through the projects UID/EMS/00667/2013, UID/EMS/50022/2013, and PTDC/EMS-PRO/4732/2014.